Anti-Spot, Lightening Effect and Cutaneous Acceptability of a Stable Anhydrous Ecobiological Formulation of 10% L-Ascorbic Acid - Abric E; Mathias J; Tardieu AS; Mateos L; Eeckhout C; Drulhon F; Ardiet N (Dove Medical Press, 2024)
Elise Abric, Jessica Mathias, Anne-Sophie Tardieu, Léa Mateos, Chantal Eeckhout, Fanny Drulhon, Nathalie Ardiet Research and Development Department, NAOS Ecobiology Company (Bioderma - Institut Esthederm - Etat Pur), Aix-en-Provence, FranceCorrespondence: Léa Mateos, NAOS Ecobiology Company (Bioderma - Institut Esthederm - Etat Pur), Research and Development Department, Aix-en-Provence, France, Email lea.mateos@naos.com